2016
DOI: 10.1111/jdi.12484
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum adipocyte fatty acid‐binding protein in women with gestational diabetes mellitus and normal pregnant women during mid‐ and late pregnancy

Abstract: Aims/IntroductionTo observe the longitudinal changes in serum adipocyte fatty acid‐binding protein (AFABP), carbohydrate, and lipid metabolism parameters in women with and without gestational diabetes mellitus (GDM) during mid‐ and late pregnancy periods, as well as to identify whether there is any association between AFABP and development of GDM.Materials and MethodsA total of 40 GDM and 240 normal glucose tolerance participants were enrolled at 24–28 weeks and completed the study. The clinical features, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 31 publications
(46 reference statements)
8
55
0
1
Order By: Relevance
“…Also, Zhang et al (40) detected higher level of AFABP during mid-and late stages of pregnancy in GDM women and concluded that AFABP might be closely related to obesity and IR in pregnancy, and is a major risk factor for GDM. Thereafter, Li et al (41) detected significantly higher expression of AFABP in serum, placenta and decidua of pregnant GDM women than in normal pregnant women.…”
Section: Discussion:-mentioning
confidence: 99%
“…Also, Zhang et al (40) detected higher level of AFABP during mid-and late stages of pregnancy in GDM women and concluded that AFABP might be closely related to obesity and IR in pregnancy, and is a major risk factor for GDM. Thereafter, Li et al (41) detected significantly higher expression of AFABP in serum, placenta and decidua of pregnant GDM women than in normal pregnant women.…”
Section: Discussion:-mentioning
confidence: 99%
“…In contrast with other adipokines, such as retinol-binding protein 4 (RBP-4) and visfatin, adiponectin is inversely correlated to type 2 diabetes mellitus and GDM [12][13][14] . However, fewer studies show that low adiponectin levels have no association with the risk of GDM 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…GDM generally results in few symptoms; however, it does in- Du crease the risk of macrosomia, preeclampsia, and perinatal death [3]. Good control of blood glucose during pregnancy may contribute to prevent the occurrence of negative gestational complications and a good feral outcome in women with GDM in the short run [4].…”
Section: Introductionmentioning
confidence: 99%